Etnobotani Tanaman Obat untuk Pengobatan Penyakit Kulit oleh Masyarakat di Kelurahan Sasa Kecamatan Ternate Selatan - Umagap, Wirda Az; Laisouw, Ruslan (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
Ethnobotany is a field that studies how people in an area use various types of plants, one of which is for traditional medicine. This treatment is usually used traditionally in Indonesia, such as ointment, but no cure has been found. Sufferers ultimately decide to seek more scientific alternative medicine, which is usually known as traditional medicine, even though they continue to experience pain. treatment carried out by people who have skin diseases and use this plant to treat their skin diseases. This research aims to determine the ethnobotany of medicinal plants in the treatment of skin diseases by the community in Sasa sub-district, South Ternate District. This type of research is exploratory or exploratory descriptive research using survey, interview or questionnaire methods conducted in the Sasa sub-district, South Ternate District. The results of the research show that in Sasa sub-district there are 15 types of plants from 11 families that can be used as medicine for skin diseases. In the interview, the processing method was to mash, cut, and then apply the affected area. Seeds, rhizomes, leaves, fruit, stems and flowers are the parts of the plant used..Keywords : Etnobotani, Tanaman Obat, Penyakit Kulit